A Study on the Selected Anthropomorphic Characteristics of Girls and Boys in Childhood and Adolescence - Akbar Taherian; Masoumeh Shojaei; Afkham Daneshfar; Maryam Sharifdoust (Vesnu Publications, 2018)
Introduction: The structural body features provide physicians, health care professionals, educators, and parents with important information like natural body development, physical activities in accordance through body size, sport talent identification, and prediction of certain diseases such as cardiovascular and cancer problems. This study was run to determine and compare the features of average body stature as height at both lying and standing positions, sitting height, and sitting height to standing height ratio. Materials and methods: Among 315,987 elementary to high school students in Isfahan City, Iran, 768 children and adolescents were selected through cluster sampling, and were categorized in four groups, according to age and gender. Postural variables were measured using a standard meter. To describe and analyze the data, one-way ANOVA, Levene, and Post Hoc tests were run at a significance level of less than 0.05. Results: Although lying height was higher than standing height, their increasing trends remained the same. Although the boys' sitting height was higher than the girls', the sitting height to standing height ratio of the boys was lower than girls. Adolescent girls and boys had the most and the least sitting height to standing height ratio, respectively. Sitting height to standing height ratio was different in each category (P < 0.001 for all). Conclusion: There was no significant difference in the mean lying height, standing height, and sitting height between boy and girl children. As to the sitting height to standing height ratio, girl adolescent with both boy and girl children were at the same level, and boy adolescent were on another. The findings have correspond to standards of Centers Disease Control and Prevention (CDCs) for height.